2019
DOI: 10.1177/0956462419855484
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gonorrhea and chlamydia in a community clinic for men who have sex with men in Lisbon, Portugal

Abstract: Men who have sex with men (MSM) are at greater risk for sexually transmitted infections (STIs). Data on MSM chlamydia and gonorrhea prevalence estimates and associated risk factors are scarce. To our knowledge, this is the first study to describe the prevalence and the determinants of both chlamydia and gonorrhea infections in MSM in Portugal. We conducted a cross-sectional study using data from 1832 visits to CheckpointLX, a community-based center for screening blood-borne viruses and other STIs in MSM. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
3
7
0
2
Order By: Relevance
“…Our findings suggest that consistent condom use for penile-anal sex could prevent more than half of incident cases and so promoting their use is an effective prevention strategy. Our estimated incidence data support the observed epidemiological data that anorectal chlamydia infection was the most common site-specific infection [ 51 , 52 ]. Our models suggested that the estimated proportion of incident chlamydia caused by all sequential activities while low (7.3–23.6%) was necessary to replicate the observed epidemiology.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that consistent condom use for penile-anal sex could prevent more than half of incident cases and so promoting their use is an effective prevention strategy. Our estimated incidence data support the observed epidemiological data that anorectal chlamydia infection was the most common site-specific infection [ 51 , 52 ]. Our models suggested that the estimated proportion of incident chlamydia caused by all sequential activities while low (7.3–23.6%) was necessary to replicate the observed epidemiology.…”
Section: Discussionsupporting
confidence: 89%
“…Another German study found a similar prevalence of NG (8.9%) but a lower prevalence of CT (9.9%), with a similar distribution across anatomical sites as seen in our study [ 7 ]. In a care-seeking sample of MSM in Portugal, prevalence of NG was 10.7% and prevalence of CT was at 7.6% less than half of the prevalence in the BRAHMS cohort [ 23 ]. The discrepancy in CT prevalence may be due in part to the different inclusion criteria for the respective studies as the Portuguese study included any care-seeking individual who had results for CT/NG tests at all three anatomical sites.…”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence was highest among anorectal STI, we also found pathogens present in both pharyngeal and urogenital samples, highlighting the need for screening at all sites. In a meta-analysis of 12 STI and PrEP use studies, among participants with positive NG tests, 13.8% had both positive anorectal and pharyngeal tests while 2.5% had positive pharyngeal, anal and urogenital tests [ 23 ]. The decision to treat asymptomatic infections with MG, NG and CT needs to weigh advantages in terms of STI sequelae with the potential damages to the microbiome caused by frequent use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that, in 2016, the global prevalence of CT and NG in 15–49-year-old men was 2.7 and 0.7%, respectively ( 1 ). Untreated CT and NG could lead to serious complications in men including epididymitis, reactive arthritis, mucosal inflammation in the oral and anorectal areas, anorectal pain, discharge, and severe scarring (mostly related to the presence of genotype L of CT) ( 2 , 3 ), and also increase the risk of the human immunodeficiency virus (HIV) transmission ( 4 ). For men, around 50% of CT cases and 10% of NG cases were asymptomatic in urethral samples, which indicates the importance of CT and NG screening ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the general population, a higher prevalence of CT and NG infections among men who have sex with men (MSM) was found in many studies ( 2 , 7 ). Extragenital CT and NG infections among MSM have become an increasingly important concern as extragenital-only infections are very common.…”
Section: Introductionmentioning
confidence: 99%